(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The innovative technology in the banking industry has been constantly evolving. Innovative technology based activities in the banking sector enable customers to avail banking services from the comfort of their own home. It enhances home based transaction of banking activities such as exchange of money. Also the customers do not have to go to bank for each transactions. Different mobile apps of different banks are coming up with new services from time to time. There applications that can be easily installed on mobile devices for providing services and facilities to customers. Nowadays, mobile apps offered by banks are working as a financial supermarket. Paperless and card less transaction are offered by many banks via mobile apps. However, customers are not utilizing mobile banking apps in a full-fledged manner. The present study analyses the impact of mobile banking in kanyakumari district